Atividade antimicobacteriana e antibiofilme de sulfonamidas complexadas com Au, Cu, Cd, Ag e Hg - Agertt, Vanessa Albertina (2016)
Mycobacterial infections including Mycobacterium tuberculosis have been increasing globally. The additional prevalence of multidrug-resistant (MDR-TB) strains and extensively drug-resistant tuberculosis (XDR-TB) stimulate an urgent need for the development of new drugs for the treatment of mycobacterial infections. Mycobacteriosis is a type of infection caused by rapidly growing mycobacteria (RGM), which can vary from localized illness, such as skin disease, to disseminated disease. Amikacin, cefoxitin, ciprofloxacin, clarithromycin, doxycycline, imipenem and sulfamethoxazole are antimicrobial drugs chosen to treat such illnesses; however, not all patients obtain the cure. The reason why the treatment does not work for those patients is related to the fact that some clinical strains present resistance to the existing antimicrobial drugs; thereby, the research of new therapeutic approaches is extremely relevant. The coordination of antimicrobial drugs to metals is a promising alternative in the development of effective compounds against resistant microorganisms. Sulfonamides complexed with Au, Cd, Ag, Cu, and Hg have shown excellent activity against a variety of microorganisms. Considering the importance of fighting against infections associated with RGM, the objective of this study is to evaluate the antimycobacterial activity of metal complexes of sulfonamides against mycobacterials. It determined the minimum inhibitory concentration (MIC) of the compounds against Mycobacterium tuberculosis and RGM, as well as their interactions with trimethoprim being determined Fractional Inhibitory Concentration Index (FICI) for each association. It also evaluated the action of sulfonamides against biofilms formed by RGM. Sulfonamides showed increased antimicrobial activity when compared to sulfamethoxazole both plantonicas cells and biofilms, and showed synergistic effect when combined with trimethoprim.